Programmable photo-responsive self-healing hydrogels for optical information coding and encryption - Wang, Yufei; Chen, Zihao; Li, Nanshu; Zhang, Hanbing; Wei, Jie (European polymer journal, 2022)
[Display omitted] •A self-healing hydrogel consists of PAM, PAA, and PDMAEMA.•Mo7 endows the hydrogel with photochromic property.•Coumarin derivative endows the hydrogel with fluorescence property.•The hydrogel can be used for optical information coding and encryption. In this study, we proposed programmable photo-responsive self-healing hydrogels containing polyacrylamide (PAM), polyacrylic acid (PAA), poly[2-(dimethylamino) ethyl methacrylate] (PDMAEMA), ammonium molybdate (Mo7), and 7–2(acryloyl hydroxypropyl)-4-methyl-coumarin (AHPMC). Because of the electrostatic interaction of PAA and PDMAEMA, the hydrogel demonstrates good self-healing properties. Moreover, we introduced Mo7 and coumarin derivative in the hydrogel, respectively, which endows the hydrogel photo-responsive properties. Under the control of UV light, PAM-AD/Mo7 hydrogel with photochromic behavior could turn atrovirens, and PAM-AD/AC hydrogel with photoluminescent properties could emit blue fluorescence. In contrast, PAM-AD hydrogel possesses no photo-responsive behavior. Based on the self-healing and photo-responsive properties of the hydrogels, the three hydrogel blocks could be programmed and healed as a whole combination. In addition, we demonstrated the application of the hydrogel in optical information coding and encryption, which possesses good information coding and encryption effect. Therefore, the photo-responsive self-healing hydrogel may have potential applications in flexible information display and encryption fields.